2020
DOI: 10.1002/jsfa.10208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the mixture of mulberry leaf powder and KGM flour on promoting calcium absorption and bone mineral density in vivo

Abstract: BACKGROUND In this paper, mulberry leaf powder (MLP) and konjac glucomannan (KGM) flour were used as raw materials, and animal experiments were designed to evaluate the effects of a mixture of MLP and KGM on bone density. The femoral bone microstructure of mice and pathological changes were observed by using micro‐computed tomography) and haematoxylin and eosin (HE) staining methods, respectively. A three‐point bending test was used to determine the biomechanical properties of the femur. RESULTS Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…However, excess protein may also have a negative feedback regulation on enzyme secretion and activity. This regulation is related to the abundance of excess protein and animals of different types 38 . It could be inferred that the opposite result might be attributed to the significant increase in the transcription level of genes related to protein metabolism under high‐protein concentration, followed by negative feedback regulation of the translation level.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…However, excess protein may also have a negative feedback regulation on enzyme secretion and activity. This regulation is related to the abundance of excess protein and animals of different types 38 . It could be inferred that the opposite result might be attributed to the significant increase in the transcription level of genes related to protein metabolism under high‐protein concentration, followed by negative feedback regulation of the translation level.…”
Section: Results and Analysismentioning
confidence: 99%
“…This regulation is related to the abundance of excess protein and animals of different types. 38 It could be inferred that the opposite result might be attributed to the significant increase in the transcription level of genes related to protein metabolism under high-protein concentration, followed by negative feedback regulation of the translation level. Alternatively, it is plausible that protein degradation occurred during the synthesis process, leading to a decrease in the translation level of relevant genes, as reported by Wu.…”
Section: Effect Of Compound Powder On the Intestinal Microbiota In Ol...mentioning
confidence: 99%
“…The body weight of the mice was measured once a week using an electronic scale, each time after fasting the mice for 12 h. The body length was measured using vernier calipers. 32…”
Section: Methodsmentioning
confidence: 99%
“…Konjac glucomannan (KGM), the main component of konjac flour, is a water-soluble dietary fiber known for its high viscosity and capacity to improve intestinal health and bolster the immune system ( Zhang et al, 2021 ; Zhang et al, 2022 ). Animal studies have demonstrated that the compound dietary fiber composed of mulberry leaf and konjac flour (CMK) can reduce the pH of the intestine, elevate the content of short-chain fatty acids (SCFA) ( Deng, Luo, Zhang, & Zhong, 2020 ) and enhance beef protein metabolism in mice consuming a high in beef-protein diet ( Deng, Zhong, Peng, & Zhu, 2023 ). In contrast to beef, fish meat is an ideal source of complete protein for the elderly due to its low-fat content, high-protein levels, and essential amino acid composition.…”
Section: Introductionmentioning
confidence: 99%